Teaching for thinking - Keefe, James W.; Walberg, Herbert J. (Reston Veriginia : National association, 1992)
This volume represents a variety of current efforts to incorporate thought-provoking methods into teaching. There are three sections. "Curriculum Developments" defines key curricular terms and offers a framework and general examples of teaching tactics. In this section, Barbara Presseisen distinguishes thinking from other cognitive activities and shows how "conation" (motivation and striving) and knowledge representation are being used to promote thinking. Robert Marzano discusses three domains (learning to learn, content thinking, and reasoning) assignable to specific subjects, and Francis Schrag describes how to promote deep thinking in the classroom. "Teaching and Assessment" describes new methods for teaching thinking and assessing student progress. Barak Rosenshine and Joseph Guenther describe "scaffolding" (temporary instructional supports), and Ann Brown and Joseph Campione urge incorporation of thinking into all school programs through "reciprocal teaching" strategies. Charles Letteri's essay focuses on assessing students' learning strengths and weaknesses as a diagnostic tool for guiding individualized and group programs to improve classroom performance. Robert Ennis discusses several tests and techniques for measuring thinking for accountability. "Concluding Perspectives" synthesizes research on practical methods of teaching thinking in essays contributed by Barry Beyer, Robert Sternberg, and James Keefe. Most chapters contain reading suggestions. (Mlh)
Keywords: Accountability; Curriculum Development; Elementary Secondary Education